13. Enhancing Music Listening in Educational Context - Iuşcă Dorina (Sciendo, 2016)
A growing body of research has shown the importance of music listening in psychological frameworks such as the construction of emotional and social identity. Nonetheless, the educational implications of this activity involve the way students use music listening for cultural development, cognitive processing and aesthetic reaction enhancement. The present study aims to review the relevant literature regarding how musical preference, a concept used mainly in music psychology, may be explored in educational contexts. Zajong's (1968) theory of repeated exposure indicates that mere exposure to a stimulus is enough to create a favorable attitude towards it. This study investigates the experimental researches focused on the conditions where repeated exposure to academic music may generate the development of musical preference.